Investigation of directional hydraulic fracturing based on true tri-axial experiment and finite element modeling. (May 2016) - Deng, J.Q.; Lin, C.; Yang, Q.; Liu, Y.R.; Tao, Z.F.; Duan, H.F.
Abstract: The initiation and propagation of directional hydraulic fracturing (DHF) was investigated based on true tri-axial experiment and finite element modeling. The influences of notch angle, notch length and injection rate on the DHF were investigated. The initiation and propagation of DHF was modeled by a 3D nonlinear finite element method. A comparison between experimental investigation and numerical modeling results indicates that there is a good correlation between unbalanced force (UF) and fracturing. UF can be used to predict the hydraulic fracture initiation and propagation.